2017
DOI: 10.1007/s00701-017-3396-5
|View full text |Cite
|
Sign up to set email alerts
|

Early recognition of aggressive pituitary adenomas: a single-centre experience

Abstract: We proposed a new and comprehensive definition of aggressive pituitary adenoma, based upon radiological, clinical and pathological features. In a selected cohort of patients, radiological invasion resulted in the most common marker to describe the aggressive behaviour of pituitary adenoma. Surgery, radiotherapy and medical treatment (the latter only in secreting adenoma) achieved disease control in half of the patients with aggressive adenoma, especially surgery in those with ACTH-oma and medical treatment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…Patients with NFPAs were older than those with functioning tumours, and the diagnosis might be delayed until mass symptoms occur as they lacked symptoms related to hormonal hypersecretion. They reported that the characteristics of aggressiveness were similar between silent adenomas and NFPAs, even separately analysing silent corticotrophinomas and gonadotrophinomas (Ceccato et al 2018).…”
Section: Endocrine-related Cancermentioning
confidence: 98%
“…Patients with NFPAs were older than those with functioning tumours, and the diagnosis might be delayed until mass symptoms occur as they lacked symptoms related to hormonal hypersecretion. They reported that the characteristics of aggressiveness were similar between silent adenomas and NFPAs, even separately analysing silent corticotrophinomas and gonadotrophinomas (Ceccato et al 2018).…”
Section: Endocrine-related Cancermentioning
confidence: 98%
“…Regarding hormone secretion, invasive tumors are more frequently non-functioning, silent corticotroph and silent subtype-three PAs (now defined plurihormonal PIT1-positive adenomas, according to the most recent WHO classification [21]), or PRL-secreting and GH-secreting [22][23][24][25][26][27][28][29][30]. Sphenoid invasion seems to be related to the size of the PA [31] and male gender [12].…”
Section: Epidemiologymentioning
confidence: 99%
“…The decision to start TMZ in pituitary carcinomas is clear ( 66 , 76 ) but in aggressive pituitary adenomas other factors such as age, previous medical therapy, radiotherapy, number of previous surgical interventions, invasion, proliferation markers, and histologic subtype of the tumor must be considered ( 66 , 84 ). The benefits of starting TMZ must outweigh the risks of repeated surgeries, re-irradiation, and potential complications with standard treatments, and in all cases, the decision must be considered from an interdisciplinary perspective ( 74 , 76 ).…”
Section: Temozolomide Treatment Outcomementioning
confidence: 99%